Morphotectonic Analysis of Sabalan Caldera and its Impact on Related River Basins and Alluvial Fans in the Northern Slopes - Aghil Madadi; Mohammad Nouhi (جغرافیا و پایداری محیط, 2020)
ne of the most interesting landforms in the Sabalan massif landscape is the 12 Kilometers caldera-shaped circular fault. The fault has affected landforms, including catchments and associated alluvial fans. The purpose of this study was to analyze the role of Sabalan Caldera in the evolution of river basins and associated alluvial fans in the northern slopes. Morphotectonic indices including Stream Gradient Index (SL), Mountain-Front Sinuosity (SMF), Valley-Floor Width to Height Ratio (VF) and Transverse Topographic Symmetry Factor (T) were used in the present study. Besides, Topographic maps 1:25000, Geological maps 1:100000, Digital Elevation Model (Dem) with resolution of 20 meters, Landsat satellite image with resolution of 30 meters, Geographic Information System (GIS), Excel, Arch Hydro10 and Envi 4.8 as research tools, have been used to provide the quantitative and qualitative analyses of morphotectonic indices. Moreover, field observations and geomorphologic evidence have been used to verify greater confidence in the results. The findings from the calculation of morphotectonic indices and field observations, also geomorphologic evidence showed that the caldera range are still tectonically active. Moreover, the drainage network map obtained from the digital elevation model, revealed that the caldera collapse has changed the pattern of the drainage networks from the radial to the central state and then to the dendritic state. Likewise, this process has increased not only the area of the catchments but also the power flow of the rivers. As a result, the rivers using a loose formation of Lahar have incised fan systems and left behind the abandoned terraces and old fans. Extended Abstract 1-Introduction The unrelenting competition among tectonic processes building topography and surface processes that tend to tear them down represents the core of tectonic geomorphology. Fan systems are usually formed where high mountains lie next to the low land. These landforms are considered as sensitive recorders of the processes that shape them. Calderas are depressions in volcanic areas or over volcanic centers. They are the productions of vast explosions or tectonic sinking, sometimes after an eruption. One of the most interesting landforms in the Sabalan massif landscape is the 12 Kilometers caldera-shaped circular fault. The fault has affected landforms, including catchments and associated alluvial fans. The purpose of this study was to analyze the role of Sabalan Caldera in the evolution of river basins and associated alluvial fans in the northern slopes. 2- Materials and Methods Morphotectonic indices including Stream Gradient Index (SL), Mountain-Front Sinuosity (SMF), Valley-Floor Width to Height Ratio (VF) and Transverse Topographic Symmetry Factor (T) were used in the present study. Besides, Topographic maps 1:25000, Geological maps 1:100000, Digital Elevation Model (Dem) with resolution of 20 meters, Landsat satellite image with resolution of 30 meters, Geographic Information System (GIS), Excel, Arch Hydro10 and Envi 4.8 as research tools, have been used to provide the quantitative and qualitative analyses of morphotectonic indices. In addition, field observations and geomorphologic pieces of evidence have been applied to verify and greater confidence of the results. 3- Results and Discussion The purpose of this study was to analyze the morphotectonics of Sabalan caldera using morphotectonic indices and field studies and its effect on the evolution and evolution of conifers and catchments in the northern slopes of Sabalan massif. Mountain-Front Sinuosity (Smf): On active mountain fronts, uplifts overcome erosional processes and produce linear, low-Sinuosity mountain fronts, whereas, on passive mountain fronts, erosional processes overcome uplifts and produce high- Sinuosity mountain fronts. The variations of this index range from one to 1.5, 1.5 to 3 and 3 to 10, indicating very high, semi-active and inactive tectonic activity, respectively. The results of calculating the mountain front sinusoidal index showed that in many parts of the Caldera range, this value is low indicating high tectonic activity. Stream Gradient Index (Sl): One of the most important indicators of the river is that it can perform better in active tectonic detection because rivers are sensitive to tectonic activity and respond rapidly to it. The results showed that the value of Sl index in the caldera range is more than 500. Irregularities in river networks, if not for lithological and climatic reasons, are related to recent tectonic activity. According to the studies on lithology and climate of the region, it was found that all catchments have the same environmental conditions. Therefore, the difference in the value of the index is related to active tectonics. Valley-Floor Width to Height Ratio (VF): According to studies, there was a significant difference with 99% confidence in the ratio of index (VF) between active and passive tectonic zones. The range of the index changes is 1< VF, 2 > VF<1, and Vf > 2, respectively, indicating very active, semi-active and inactive tectonics, respectively. The results of this index showed that Khyav and Karkari basins with VF, 0.81 and 0.74 have high tectonic activity. The onar and Shirvan Valley watersheds have semi-active tectonic activity with VF, 1.35 and 2, respectively. Transverse Topographic Symmetry Factor (T): The value of this index in the symmetric basins is equal to zero which approaches 1 as the asymmetry increases. The value of this indicator is close to 1 in all basins, indicating the probability of tectonic activity, although it cannot individually confirm that. However, according to other indices which indicate tectonic activities, the basin can be tectonically recognized as an active one. Morphology of alluvial fans of the region: Field studies of the alluvial fans surfaces of the region show that the apex of all alluvial fans in the region has been severely incised by drainage networks. The reason for incising the apex of the alluvial fans is attributed to the tectonic activity of the Sabalan Mountain Caldera. According to the study, it was found that if the tectonic movements occur at the apex of alluvial fans, incised apex of the alluvial fans take place and embayment of front Mountain happens, although if the uplift of mountains takes place in the source area and away from the apex, they will be formed near the front of the mountain without entrenchment. 4- Conclusions The Caldera fault has created two mountain fronts in the Sabalan landscape. One is a tectonically active inland mountain front that has its signs and symptoms, including numerous cliffs, Waterfall, and another is a tectonically inactive mountainous front that is inactive having its signs and symptoms, including incised the apex of the alluvial fans and embayment of the mountain front. Moreover, the results of the calculation of Stream Gradient Index (SL), Mountain-Front Sinuosity (SMF), Valley-Floor Width to Height Ratio (VF) and Transverse Topographic Symmetry Factor (T), confirm the results.